Synthesis and Study Biological Activity of Some New Isoxazoline and Pyrazoline derivatives - Al-Rawi, Muna S.; Tomma, Jumbad H.; Abdullah, Rana M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work involves synthesis of novel Schiff bases derivatives contining isoxazoline or pyrazoline units starting with chalcons . 4-Aminoacetophenone was reacted with 3-nitrobenzaldehyde in basic medium giving chalcone [I] by claisen-schemidt reaction. The chalcone [I]  was reacted with hydroxylamine hydrochloride giving isoxazoline [II]  in basic medium. The chalcone [I] could also react with hydrazitne hydrate to give pyrazoline [III]  . The novel Schiff bases with structural formula [IV] and [V] were prepared by the reaction of amino compounds ; isoxazoline [II] and pyrazolines [III] with p-substituted aldehydes or p-subsituted ketones, respectively in dry benzene using drops of glacial acetic acid as a catalyst with reflux. All the synthesized compounds have been characterized by melting points , FTIR and 1HMNR (of some of theme) spectroscopy. The biological activity of  all compounds was examined against antibacterial ; gram(+) and gram(-).